THE Pengaruh Debt To Equity Ratio, Economic Value Added Dan Current Ratio Terhadap Return Saham Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bei Tahun 2022-2024 - Matondang, Roma Uli Tua Br; Irama, Ova Novi; Wardany, Sri; Harahap, Ardhansyah Putra (STIE Amkop Makassar, 2025)
This study aims to examine the effect of Debt to Equity Ratio (DER), Economic Value Added (EVA), and Current Ratio (CR) on Stock Return in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2022–2024. This research is a quantitative study. The sampling technique used was purposive sampling, resulting in 11 companies with a total of 33 observation data during the research period. The data used are secondary data obtained from financial statements and stock prices. The analysis method employed includes simple linear regression and multiple linear regression, as well as a series of classical assumption tests to ensure data feasibility. Data processing was carried out using SPSS version 31. The results of the study show that partially, the Debt to Equity Ratio (DER) has a positive and significant effect on stock return, and the Current Ratio (CR) also has a positive and significant effect on stock return. Meanwhile, Economic Value Added (EVA) has no significant effect on stock return. Based on the simultaneous test (F-test), all three independent variables were found to have a significant effect on stock return simultaneously.